Eksistensi Budaya Bali di Tengah Kemajemukan Budaya di Kelurahan Tangkiling, Palangka Raya, Kalimantan Tengah - Ni Nyoman Rahmawati (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
This study analyzed forms of social interaction and the existence of Balinese culture in multicultural communities in Tangkiling Village, Palangka Raya City, Central Kalimantan. The issue discussed with intercultural theory interaction with descriptive qualitative method. The results showed that the form of social interaction carried out by Balinese transmigrants in Tangkiling in the religious field was tolerance based on Tat Twam Asi, in the social sector developing a helping attitude, forming a farmer group named Sari Bumi Farmer Group, and actively joined in the membership of the Neighbourhood Security System. Competition and conflict also occur but can be managed properly so that it does not become an open conflict. These affect of Balinese culture existence in the Tangkiling, including the existence of sanggah-shrine, the concept of ngayah (religious volunteer), the tradition of annual giant-idol of ogoh-ogoh parade, and the use of decorated bamboo penjor usage. These make Balinese culture sustainable in the midst of multicultural and religious plurality.